2014
DOI: 10.1016/j.taap.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic inhibits hedgehog signaling during P19 cell differentiation

Abstract: Arsenic is a toxicant found in ground water around the world, and human exposure mainly comes from drinking water or from crops grown in areas containing arsenic in soils or water. Epidemiological studies have shown that arsenic exposure during development decreased intellectual function, reduced birth weight, and altered locomotor activity, while in vitro studies have shown that arsenite decreased muscle and neuronal cell differentiation. The sonic hedgehog (Shh) signaling pathway plays an important role duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 84 publications
2
15
0
Order By: Relevance
“…Developmental exposure to heavy metals reduces NSC proliferation and/or differentiation in the adult brain [14,23,42,49,50,53]. We have demonstrated that perinatal exposure of 50 µg/L arsenic (through all three trimesters of development) results in reduced differentiation but not proliferation of NSCs in adult male mice [56,60]; these findings are corroborated by other studies using in vivo and in vitro models of arsenic exposure at different time points [34,35]. Additionally, arsenic-induced deficits in neuronal differentiation are associated with reduced expression of neural-specific transcription factors in the adult [20,56,61,63], yet the effect of arsenic on the regulation and expression of transcription factors during embryonic neurogenesis has not been studied to date.…”
Section: Introductionsupporting
confidence: 83%
“…Developmental exposure to heavy metals reduces NSC proliferation and/or differentiation in the adult brain [14,23,42,49,50,53]. We have demonstrated that perinatal exposure of 50 µg/L arsenic (through all three trimesters of development) results in reduced differentiation but not proliferation of NSCs in adult male mice [56,60]; these findings are corroborated by other studies using in vivo and in vitro models of arsenic exposure at different time points [34,35]. Additionally, arsenic-induced deficits in neuronal differentiation are associated with reduced expression of neural-specific transcription factors in the adult [20,56,61,63], yet the effect of arsenic on the regulation and expression of transcription factors during embryonic neurogenesis has not been studied to date.…”
Section: Introductionsupporting
confidence: 83%
“…Together, these results confirm the teratogenicity of iAs as reported previously based on animal studies (Hood et al, 1977;Leonard & Lauwerys, 1980;Chaineau et al, 1990;Machado et al, 1999). In contrast, recent reports claimed ESC differentiation into cardiomyocytes, skeletal muscles and neurons was impaired or inhibited by iAs exposure (Liu & Bain, 2014;Rebuzzini et al, 2015;Wang et al, 2015). However, we did not investigate the directed differentiation of ESCs into specific cell lineages in the presence of iAs.…”
Section: Discussionsupporting
confidence: 91%
“…Shh signaling plays a fundamental role in cell differentiation, cell proliferation, and tissue polarity (Liu and Bain, 2014;Gomes et al, 2015;Islam et al, 2015). To investigate the effect of MeCP2 on Shh signaling in SMMC-7721 cells, we firstly examine the expression profiles of patched1 (PTCH1), a major component of the Shh pathway, as well as Shh and GLI1.…”
Section: Mecp2 Modulates the Shh Signaling Pathway In Smmc-7721 Cellsmentioning
confidence: 99%